2021
DOI: 10.52711/0974-360x.2021.00644
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization of New Polytriazole Derivatives from Polyacryloyl chloride and Theoretical with Corrosion Inhibitor Study for Stainless steel in acidic medium

Abstract: The purpose of the study is to synthesize and characterize a new polytriazole derivative from polyacryloyl chloried, first reaction of polyacryloyl chloride with hydrazine hydrate in the presence of DMF as a solvent to obtained acid hydrazide (1) than reacted with different amide to give poly 1,2,4-triazole derivatives(1a-1c). Newly synthesized compounds were characterized by spectral methods [13C-NMR, 1H-NMR, and FTIR] and calculated some of its physical properties. Also, we worked theoretical study involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Physical characteristics, 1 H-NMR, 13 C-NMR, FT-IR spectroscopy, and other methods were used to characterize and identify the produced compounds. The newly created compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) were based in part on the well-known antiinflammatory medication levofloxacin. The Swiss ADME server was used to perform computational techniques, such as ADME studies, in order to forecast the pharmacokinetics of the novel drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical characteristics, 1 H-NMR, 13 C-NMR, FT-IR spectroscopy, and other methods were used to characterize and identify the produced compounds. The newly created compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) were based in part on the well-known antiinflammatory medication levofloxacin. The Swiss ADME server was used to perform computational techniques, such as ADME studies, in order to forecast the pharmacokinetics of the novel drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The Swiss ADME server was used to perform computational techniques, such as ADME studies, in order to forecast the pharmacokinetics of the novel drugs. To assess the selectivity of created compounds towards the COX-2 enzyme, the results showed that all compounds met the Lipinski rule of five compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Higher PLP fitness values than the reference compound are predicted by docking studies for ligand interactions with COX-2 protein to bind with amino acids in the active pocket (Levofloxacin ).…”
Section: Introductionmentioning
confidence: 99%